2019
DOI: 10.3847/1538-4357/ab3f32
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Stars and Black Holes in the Small Magellanic Cloud: The SMC NuSTAR Legacy Survey

Abstract: We present a source catalog from the first deep hard X-ray (E > 10 keV) survey of the Small Magellanic Cloud (SMC), the NuSTAR Legacy Survey of the SMC. We observed three fields, for a total exposure time of 1 Ms, along the bar of this nearby star-forming galaxy. Fields were chosen for their young stellar and accreting binary populations. We detected 10 sources above a 3σ significance level (4-25 keV) and obtained upper limits on an additional 40 sources. We reached a 3σ limiting luminosity in the 4-25 keV ban… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 112 publications
1
21
0
Order By: Relevance
“…Table A1 shows the observations made by Chandra, NuSTAR and Suzaku. NuSTAR was the only one to successfully register strong pulsations from SXP 305 which was also reported by Lazzarini et al (2019) on 12th March 2017. The pulse profile for the same was a single broad peak.…”
Section: X-ray Variabilitymentioning
confidence: 64%
See 1 more Smart Citation
“…Table A1 shows the observations made by Chandra, NuSTAR and Suzaku. NuSTAR was the only one to successfully register strong pulsations from SXP 305 which was also reported by Lazzarini et al (2019) on 12th March 2017. The pulse profile for the same was a single broad peak.…”
Section: X-ray Variabilitymentioning
confidence: 64%
“…The 15.3 s pulse period of SXP 15.3 was derived by Lamb et al (1999) through the analysis of ROSAT and BATSE data. The detection of the 305 s pulse period of SXP 305 has for a long time proved elusive, having only been detected recently using NuSTAR observations (Lazzarini et al 2019). In this paper we investigate the origin of recent outbursting behaviour coming from the combined field of both sources as seen from Swift XRT observations.…”
Section: Introductionmentioning
confidence: 98%
“…The recurring time-scale of the outbursts has a range ∼1150-1300 d and last for ∼700-750 d. This remarkable variability seen in the photometric light curves is believed to be an indicator of size and structural changes of the Be disc (Rajoelimanana, Charles & Udalski 2011). While similar patterns in the photometric variability have been seen in BeXB systems such as CXO J005215.4−731915 (Schurch et al 2011;Lazzarini et al 2019), the large amplitude of X0103 is atypical of the known systems. Fig.…”
Section: Swiftmentioning
confidence: 81%
“…1) are generally rare in BeXBs. Lazzarini et al (2019) suggested that the ∼1180 d peak separation of the OGLE outbursts in the BeXB system, CXO J005215.4-731915, to be attributable to the orbital period. This is in contrast to earlier analysis performed by Schurch et al (2011) on the same source, where it was suggested that the long-term periodicity is due to structural changes in the disc.…”
Section: Is the Recurrence Time Of The Optical Outbursts Due To The Omentioning
confidence: 99%
“…This remarkable variability seen in the photometric lightcurves is believed to be an indicator of size and structural changes of the Be disc (Rajoelimanana et al 2011). While similar patterns in the photometric variability have been seen in BeXB systems such as CXO J005215.4−731915 (Schurch et al 2011;Lazzarini et al 2019), the large amplitude of X0103 is atypical of the known systems.…”
Section: Long Term Ogle Lightcurvementioning
confidence: 64%